Pengembangan Interaksi dan Perilaku Sosial Terhadap Pendidikan Anak Usia Dini di Abad 21 - Mushab Al Umairi Mushab (Institut Agama Islam Negeri Madura, 2023)
This research is motivated by the inability of early childhood in social interaction and good social behavior towards the environment, school, family and society in the 21st century (Modernization Era). To help reduce a child's disability in social interaction and good social behavior. therefore, it takes the efforts of help from adults. In providing this assistance, parents or teachers should understand the process of developing social interaction and social behavior towards early childhood. This study aims to determine the development of social interaction and social behavior towards early childhood education in the 21st century. The type of research used in this study is a type of field research (Field Research). Then to obtain the research data using the method of observation, interviews, and documentation. This research was analyzed using descriptive qualitative (in the form of opinions or written opinions from people and the actions observed). The conclusion of this study is that providing good social interaction and social behavior will have a positive impact on early childhood education in the 21st century. Keywords: Social Inteaction; Social Behavior; Early Chilhood Education